Analysis of dislocation line tilt in GaN single crystal by Raman spectroscopy. (27th November 2020) - Kokubo, Nobuhiko; Tsunooka, Yosuke; Inotsume, Sho; Fujie, Fumihiro; Onda, Shoichi; Yamada, Hisashi; Shimizu, Mitsuaki; Harada, Shunta; Tagawa, Miho; Ujihara, Toru
Abstract: The strain field of the tilted threading dislocation (TD) in a hydride vapor-phase epitaxy-grown c -plane (0001) GaN single crystal is demonstrated using Raman spectroscopy. In the two-dimensional mapping image of the E2 H peak shift around TDs, high-contrast areas corresponding to pairs of high and low wavenumber regions of the peak shift are observed, and the edge component of the Burgers vector can be specified. Deformed contrast areas extending in the specified direction are also observed. This deformed contrast region indicates tilted dislocations since 2D mapping also detects strain deep below the surface due to the transmission of the laser beam. Simulation of the E2 H peak shift mapping around the TD, tilted at 0° and 60° in the 11 2 ̄ 0 direction and having a Burgers vector b = 1 / 3 11 2 ̄ 0, is also performed. The simulation of the 60° tilted dislocation shows that the contrast extends in one direction. The line profiles of the E2 H peak shift by simulation are in agreement with the experimental results. We propose that the dislocation line tilt can be analyzed from the 2D Raman mapping images.